Ultrasound in Medical Applications - Hamdaney, Nadia Adel Saeed Al; Abdullah Abdul, Rosul Salem; Abdullah Algailany, Marwa Ammar; Mohammed Ibrahim, Mohammed Hussein; Khalil Altaee, Sarah Ghassan (American Journal of Botany and Bioengineering, 2024)
Ultrasound technology has revolutionized medical diagnosis and treatment in various medical disciplines. This paper provides an overview of ultrasound principles, technological advances, and its wide-ranging applications in medicine. Ultrasound, based on sound waves with frequencies above the human audible range, provides non-invasive imaging capabilities with real-time visualization of internal body structures. The development of high-resolution imaging technologies has enhanced diagnostic accuracy and enabled accurate anatomical assessments. Furthermore, ultrasound, such as Doppler, facilitates the assessment of blood flow dynamics, which aids in the diagnosis of cardiovascular diseases and vascular malformations. Beyond diagnosis, ultrasound-guided interventions have become common in minimally invasive procedures, including biopsies, injections, and surgeries, with positive impact on public health. In addition, therapeutic ultrasound techniques, such as high-intensity focused ultrasound (HIFU) and ultrasound-mediated drug delivery, have emerged as promising modalities for targeted tissue ablation and topical drug administration, respectively. In conclusion, ultrasound technology continues to evolve, offering versatile solutions for medical imaging, diagnosis, interventions, and treatments, with significant implications for improving patient care and advancing medical research.